Интегро-дифференциальные уравнения с многозначными решениями - Плотников, А.В.; Тумбрукаки, А.В. (Український математичний журнал, 2000)
Доводиться теорема існування та єдиності класичного розв'язку для інтегро-диференціального рівняння з похідною Хукухари, а також обґрунтовується одна із схем усереднення для такого типу рівнянь в стандартному вигляді. We prove a theorem on the unique existence of a classical solution of an integro-differential equation with Hukuhara derivative. We also justify an averaging scheme for equations of this type in the standard form. Integro-differential equations with multivalued solutions